2012
DOI: 10.1093/bioinformatics/bts352
|View full text |Cite
|
Sign up to set email alerts
|

ModuLand plug-in for Cytoscape: determination of hierarchical layers of overlapping network modules and community centrality

Abstract: The plug-in and its user guide can be downloaded freely from: http://www.linkgroup.hu/modules.php.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(134 citation statements)
references
References 45 publications
0
134
0
Order By: Relevance
“…To identify important hubs in the network, centrality was assessed. "Betweenness centrality" measures how often a path passes through a specific node while moving from one node to another (22).…”
Section: Methodsmentioning
confidence: 99%
“…To identify important hubs in the network, centrality was assessed. "Betweenness centrality" measures how often a path passes through a specific node while moving from one node to another (22).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that many proteins have a modular architecture, with modules corresponding to (often functionally distinct) subdomains. Residues between modules tend to be conserved and more rigid, and are thought to be involved in allosteric communication [66][67][68][69]. Several studies have employed the concept of modules or a related notion [69][70][71].…”
Section: Methods To Identify Allosteric Pathways In Intraprotein Netwmentioning
confidence: 99%
“…We may use a number of centrality measures [194], including perturbation-based or game-theoretical assumptions [115,195], to find the level of importance of proteins and pathways in interactomes and signaling networks, and important amino acids in their extensions to atomic level resolution [69].…”
Section: Possible Methods To Identify Allo-network Drug Targetsmentioning
confidence: 99%
“…Extending these observations further in a former study [54] we used the ModuLand program package [76] and its Cytoscape plug-in [93] to identify extensively overlapping network modules of the protein-protein interaction network of S. cerevisiae under fast-growing conditions and after various stresses. Upon a 15 minute, heat shock at 37°C, the overlap between yeast interactome modules became significantly smaller.…”
Section: Short-term Adaptive Changes Of Cellular Network: Changes Ofmentioning
confidence: 99%